MODEL HIPOTETIK ”PEER COUNSELING” DENGAN PENDEKATAN REALITY THERAPHY UNTUK SISWA SLTA (SATU INOVASI BAGI LAYANAN KONSELING DI SEKOLAH) - Erhamwilda Erhamwilda (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
Quantity and the quality of counseling services for senior high school students are still much lower that they are expected is suspected to be due to their low skill in mastering counseling approaches in one side and students’ tendency to consult their peers. Researches prove that peer counseling is more effective in developing students’ personality growth and solving several child, teenager and even parents’ problems. Reality Approach Counseling, a present-based orientation and realistic thinking encouragement, is believed to be appropriate for teenagers and therefore can be promoted as one of innovated techniques in carrying out peer counseling services in senior high schools.Kata kunci: peer counseling, konseling pendekatan realitas